Efficient and selective film separation of organism/salt with graded nanofluid channels stimulated by a rigid crystal skeleton. Issue 5 (18th January 2023) - Zhang, Tianmeng; Tan, Hao; Du, Yao; Huang, Haimeng; Shen, Mingxia; Liu, Xing; Wang, Zhongchang; Zhang, Jianfeng
Abstract : Polymer microspheres equipped with a porous skeleton network to build fluid channels for efficient water treatment. Abstract : The critical demand for zero wastewater discharge and water purification has stressed the importance of appropriate membrane material design and applications. The design of porous nanopores in films is a promising solution for improving the film's low flux and poor selectivity. Therefore, a porous crystal skeleton-stimulated hard/soft film is designed and used for dye/salt separation. Specifically, an amino-modified zeolitic imidazolate framework (ZIF-8) was used as a porous rigid skeleton on the surface of polypyrrole submicron spheres (PMs) and then anchored onto a PBC (polypyrrole-coated-bacterial-cellulose) layer by amide crosslinking as well as zinc ion coordination. Through such a design, abundant graded nanopores and fluid channels were obtained and greatly enhanced the transportation of water molecules across the film. Even in a high salinity environment (1–5%) of NaCl, Na2 SO4, and CaCl2, the maximum water permeability of 1500 L m −2 h −1 bar −1 (through dead-end filtration) and 620 L m −2 h −1 bar −1 (through crossflow filtration) was obtained with the complete rejection of most typical dyes. It should be pointed out that such an outstanding permeability is 1–2 orders of magnitude higher than that reported in the literature and found to be stable even after 10 periodic operations. Furthermore, the transfilm diffusion behavior of dyes and salts driven by multimodes (concentration difference and electric field) is also explored for the first time, providing usability support for operability in different application environments. The dynamics theory simulation indicated that the porous skeleton provides a multiscale fluid channel for ion diffusion transport, which greatly enhances water permeability and selective barrier to dyes. This work provides a new strategy and reveals the importance of nanoporous channels for designing efficient water purification–separation films.